Benefits and Mode of Action of Various Hasta Mudra - Dhiman , Sonia; Chaudhary, Vijay; Jagota, Ankush (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: In this modern era, our lifestyle is changed and become sedentary. Lack of physical exercise, faulty dietary habits, increased stress, and environment changes lead to many diseases. Everybody is fed up by taking so many medicines. Hence, people are showing interest in drugless therapies. Practicing Hasta mudra is totally drugless and cost less. Aim: The aim of this article is to describe the preventive and curative benefits of Various Hasta Mudra and to explain the mode of action of Various Hasta Mudra. Materials and Methods: Various benefits and modes of action of Hasta Mudra have been explained on the basis of classical texts and literature. Results: With regular practice of Hasta mudra, various diseases can be prevented and cured. Discussion: Mudra should be performed for at least 45 min in a day. Conclusion: Hasta Mudra is helpful in Mudhra therapy can control stress, depression, anxiety, fear and promotion of mental health and happiness prevention and cure of many diseases. in Mudra.[3] In Shiva Samhita, it is mentioned that just by practicing The word mudra is a Sanskrit word which has the meaning “gesture” or “attitude.” Mudra can be described as emotional, psychic, devotional, and esthetic gestures or attitudes. Mudra are attitudes of energy flow, which help in linking person’s pranic force with universal or cosmic force.[1] The literal meaning of mudra is the expression of internal feelings by way of different postures of fingers, palms, hands feet, and or body. This is an integral part of yoga and a scientific knowledge of spirituality and physical well. There are different types of Mudra, but in this article, we are discussing only about Hasta Mudra. By doing Hasta mudra, subtle hand and finger movements make important connections in the nervous system and stimulate specific energy pathways. In Hatha Yoga, there are 10 mudra which are mentioned as Jaramarananashaka.[2] In Gheranda Samhita, there are 25 Mudra and according to it, various eye and body positions (Asana) and Locks (Bandha) are also included